Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen: Studi Kasus Pada Seblak Kedai Warna Di Permata Biru - Salwa Fatimah Azahra; Deri Apriadi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the extent of the influence pf product quality and service on customer satisfaction of Seblak Kedai Warna in Permata Biru. A quantitative approach was used with data collection methods through questionnaries distributes online during March to April 2025. The sampling terchnique used cluster random sampling, and data analysis was carried out by multiple linear regression using SPSS version 25. The results showed that product and service quality have a significant influence on customer satisfaction. This finding confirms the importance of improving product and service quality for the sustainability of culinary UMKM